2016
DOI: 10.1111/mec.13637
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to low temperatures in the wild tomato species Solanum chilense

Abstract: Molecular adaptation to abiotic stresses in plants is a complex process based mainly on the modifications of gene transcriptional activity and the alteration of protein-protein interactions. We used a combination of population genetic, comparative transcriptomic and plant physiology approaches to investigate the mechanisms of adaptation to low temperatures in Solanum chilense populations distributed along Andean altitudinal gradients. We found that plants from all populations have high chilling tolerance, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 79 publications
(182 reference statements)
4
54
0
1
Order By: Relevance
“…These populations experience considerable variation in geographic parameters like precipitation and temperatures. It is known that S. chilense has a clear demographic pattern and signs of adaptations to climatic differences between different populations (Fischer et al, 2011; Fischer et al, 2013; Nosenko et al, 2016). A demographic pattern of North–South colonisation is observable with larger and more diverse populations in the north of the range and smaller and less diverse populations in the south.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These populations experience considerable variation in geographic parameters like precipitation and temperatures. It is known that S. chilense has a clear demographic pattern and signs of adaptations to climatic differences between different populations (Fischer et al, 2011; Fischer et al, 2013; Nosenko et al, 2016). A demographic pattern of North–South colonisation is observable with larger and more diverse populations in the north of the range and smaller and less diverse populations in the south.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, S. chilense shows clear climatic adaptations. Populations from drier regions are responding faster to drought (Fischer et al, 2013) and individual populations found at high altitudes (>3,000 m) show higher freezing tolerance (Nosenko et al, 2016)  S. chilense has also been the source of resistance loci against the fungus Verticilium dahliae (Tabaeizadeh et al, 1999) and against various viruses (Griffiths & Scott, 2001; Ji et al, 2007; Verlaan et al, 2013). Seeing that S. chilense occurs in such a wide range of habitats and that the species shows specific signs of local climatic adaptations, we wondered whether we could find variation for pathogen resistance as well.…”
Section: Introductionmentioning
confidence: 99%
“…Solanum chilense occurs in southern Peru and northern Chile. Local adaptation to abiotic and biotic stresses in S. chilense or its sister species is indicated, first, by signatures of positive selection in genes involved in cold-and drought-stress response (Xia et al, 2010;Fischer et al, 2013;Nosenko et al, 2016;B€ ondel et al, 2018), second, by balancing selection in several genes of the Pto resistance pathway providing resistance to Pseudomonas sp. (Rose et al, 2011), and, third, by variable resistant phenotypes against filamentous pathogens across populations .…”
Section: Introductionmentioning
confidence: 99%
“…The function of ICE1 is conserved in many plant species, and the heterogeneous expression of the rice, maize, or tomato ICE1 orthologs in Arabidopsis enhanced plant freezing tolerance (Nosenko et al ; Deng et al ; Lu et al ). ICE2, a paralog of ICE1, is also involved in regulating CBF expression and freezing tolerance (Fursova et al ).…”
Section: Transcriptional Regulation Of the Cbfs In The Cold‐signalingmentioning
confidence: 99%